Nanosponges: The Advant in Pharmaceutical Field for Optimial Delivery of Medications. - AJPRD, Zambare Swapnil D.; Sontakke Shrikrushn B; Borkar Smita P.; More Priti U; Shinde Snehal M (Asian Journal of Pharmaceutical Research and Development, 2025)
Fast developments in nanotechnology have given rise to a novel and promising medicine delivery method called nanosponges. These nanostructures meet the need for accuracy and controlled release in medication management by being able to carry a variety of tiny drug molecules and being delivered by oral, topical or parenteral methods. In particular, because of their high selectivity, biocompatibility, degradability, and capacity to provide a sustained release of the medicines, nanosponges hold the potential to significantly enhance cancer therapy. The advantages of the nanosponge system extend beyond cancer treatment; it is suitable for treating a wide range of illnesses, such as infections and autoimmune diseases. The sponge-like structure of nanosponges, which can hold a wide range of drug molecules, is the main component of their drug delivery mechanism. The regulated release of the medication takes place at the target spot, which is reached after the pharmaceuticals are loaded into the nanosponges and circulate throughout the body. Because of their similar size to viruses, which enables them to interact with cells at the minuscule scale and efficiently transport medications throughout the body, nanosponges are also good drug delivery vehicles. In the field of topical drug administration, their use is especially noteworthy for the treatment of skin diseases and fungal infections. All things considered, the nanosponge drug delivery system has many benefits over conventional medicine administration methods, such as the ability to deliver drugs precisely where they are needed, increased bioavailability, less adverse effects, and improved therapeutic efficacy. The pharmaceutical industry is still heavily researching this dynamic delivery system, which offers improved therapy alternatives for patients with a variety of ailments.